Towards Implementation of Sociology Theory in Management Accounting Research - Sofik Handoyo; Syaiful Anas (Journal of Accounting Auditing and Business, 2018)
This article aims to give another perspective for Management accounting scholars implement sociology theories in their researchers. Traditionally, accounting researchers have been conducted relying on accounting theory, management theory, economic theory, and psychological theory. However, in line with popularity academic research that involves the interdisciplinary field of study, it is, therefore, the possibility to adopt another perspective of theory from a related discipline. Since Management accounting discipline is closely associated with the organization and behavior of an individual within the organization, sociology theory is considered fit to be adopted. This article will figure out potential research in management accounting discipline using framework sociology theory.